Biochemical markers of nutrition in elite-marathon runners - Crespo, R.; Relea, P.; Lozano, D.; Macarro-Sanchez, M.; Usabiaga, J.; Villa, L. F.; Rico, H. (The Journal of Sports Medicine and Physical Fitness, 1995)
Although diet surveys have been made in marathon runners, as far as we know their nutritional state has not been evaluated by measurement of the so-called biological markers of nutrition, such as transferrin, retinol-binding protein, and prealbumin. We measured the levels of these substances in 18 marathon runners (11 men and 7 women; mean age 26.9 +/- 4.0 years) and in 22 controls (13 men and 9 women; mean age 26.2 +/- 3.6 years). As some of these markers are zinc-dependent, serum zinc levels also were measured. Likewise, serum calcium, phosphorus, and magnesium levels were measured to ascertain the athletes' mineral status. Calcium corrected for proteins, phosphorus, magnesium, and zinc did not differ between the marathon runners and controls; likewise, there were no differences in serum ferritin and glucose levels. As regards the biological markers of nutrition, prealbumin levels were higher in athletes than in controls (31.7 +/- 4.7 vs 28.9 +/- 4.8 mg/dl, p < 0.025). There were no differences in the levels of retinol-binding protein and transferrin between runners and controls